Penguraian Konsep Tanggung Jawab Dalam Filsafat Hukum: Dari Dimensi Individu Ke Masyarakat - Putri, Audrey Bilbina; Cherieshta, Jocelyn; Rasji, Rasji (Peneliti.net, 2024)
The concept of responsibility plays a central role in legal philosophy, shaping views on justice in society and legal systems. Since antiquity, philosophers such as Plato and Aristotle have raised fundamental questions regarding individual responsibility in the context of law. They considered whether individuals have a moral obligation to abide by laws and social norms. The literature study method will be the main approach in this research to examine in detail the development of the concept of responsibility in the context of legal philosophy and explore how this concept has been applied in legal practice over time. To determine the differences and similarities in the context of the concepts of individual responsibility and societal responsibility in legal philosophy. This article demonstrates the importance of the concept of responsibility in designing a just and sustainable legal system in a complex and globally connected society